Approximate Torsional Analysis of Curved Box Girders by the M/R-Method - Tung, David H.H.; Fountain, Richard S. (Engineering Journal, 1970)
Curved bridges are becoming increasingly prevalent in highway construction because of improved geometric designs and construction techniques. The current trend in this type of structure is to shape the girders so that they follow the curvatures of the horizontal alignment, creating a continuous flow of the major structural elements. While the appearance and structural efficiency are often enhanced by the use of curved girders, the analysis and design of these members are likely to be more complicated, which, in some cases, may be the only major factor that prevents the adoption of such a system. It is desirable, therefore, to develop approximate methods which may help practicing engineers overcome this hindrance. The objective of this paper is to present to design engineers a simplified method for the torsional analysis of single-span or continuous curved box girders, which, by virtue of their excellent strength in resisting torsion, are generally recognized as ideal supporting elements for horizontally curved structures. The accuracy and limitations of the approximate method, as well as the effects of the various parameters inherent in the problem, are discussed herein. The results are then compared with those obtained in exact solutions based on the transfer matrix method.